Recent Advancements in Radar Imaging and Sensing Technology - Samczynski, Piotr; Giusti, Elisa (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The aim of this Printed Edition of Special Issue entitled "Recent Advancements in Radar Imaging and Sensing Technology" was to gather the latest research results in the area of modern radar technology using active and/or radar imaging sensing techniques in different applications, including both military use and a broad spectrum of civilian applications. As a result, the 19 papers that have been published highlighted a variety of topics related to modern radar imaging and microwave sensing technology. The sequence of articles included in the Printed Edition of Special Issue dealt with wide aspects of different applications of radar imaging and sensing technology in the area of topics including high-resolution radar imaging, novel Synthetic Apertura Radar (SAR) and Inverse SAR (ISAR) imaging techniques, passive radar imaging technology, modern civilian applications of using radar technology for sensing, multiply-input multiply-output (MIMO) SAR imaging, tomography imaging, among others.